Frequency of HTN in subjects with Sedentary Life Style in residents of Gujri town, District Sanghar - Ghulam Mustafa Rajput, Altaf Khan, Amir BuxDetho, Abdul Rahim Mangrio, Abdul SattarKhoso, RehnazShaikh (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
OBJECTIVE: To Frequency of HTN in subjects with sedentary life style among the local residents of Gujri town, District Sanghar. Design: Cross-sectional survey, Place: conducted at Gujri town of Sanghar district; Duration: from 05* October, 2017 to 05‘ December, 2017 for duration of three (03) months. Subjects: 200 participants were enrolled out of which 170 participants were approached having sedentary life style behaviors. Methodology: after permission from the male and female subject were enrolled and designed proforma filled. Subjects not willing for inclusion were excluded from study. RESULT: Study statistics reveals sedentary behavior counts fourth one leading cause of non-communicable diseases, hypertension. 609c participants with sedentary behavior were not known about the consequences of sedentary life, while 80’ o participants were with pre-hypertension that were unaware. COCLUSION: The risk of life threatening conditions like HTN can be reduced by providing the awareness to the population about the benefits of physical activity as well as about the unwanted effects of sedentary life style.